Duty, Distress, and Organ Donation - Milliken, Aimee (The Hastings Center report, 2014)
A man of twenty-two is admitted to an intensive care unit (ICU)after intentionally overdosing on Tylenol. The nurse asks the intensivist on call if someone from the local organ procurement organization should be called in to speak to the family, given a worsening clinical picture and the likelihood that the patient will progress to brain death. The patient's condition is such that multiple organs, including his heart and lungs, could be donated. The intensivist instructs the nurse not to call, as he wishes to have an end-of-life discussion with the parents. He believes that the parents should know that death is imminent and that further interventions will not save their son. He argues that introducing the OPO at this point will cause the family more distress. He wants the parents to be able to give their son a peaceful death without additional stressors. What are the broader implications of not calling the OPO at this juncture? Does the nurse involved have an ethical obligation to override the intensivist's instructions by calling the OPO? Should the fact that multiple healthy organs could be harvested from this patient's body have any bearing on the decision to call the OPO?